Comparative anatomy of stems and leaves in some species of the South American genus Chrysolaena (Vernonieae, Asteraceae) and taxonomic implications - Sosa, Maria de Las Mercedes (2013)
Vegetative anatomical features are poorly known in the South American genus Chrysolaena. In this study, leaves and stems of six Chrysolaena species were described and compared morphologically and anatomically using diaphanization, microtome serial sectioning, and scanning electron microscopy. The species differed in leaf epidermis, type of stomata, shape of anticlinal walls of epidermal cells, trichome density, and presence or absence in stems of small air spaces in the cortical parenchyma and of druse-shaped oxalate crystals. Furthermore, glandular trichomes and three types of non-glandular trichomes with different number of basal cells were identified on leaves and stems. Collectively, these features proved instrumental to discriminate among the six studied species, suggesting that leaves and stems of Chrysolaena can represent a source for taxonomically useful characters in the genus. We also discuss anatomical features in relation to the environmental conditions of their habitats.